Efficacy of crystalline methionine and microencapsulation methionine in diets for Pacific white shrimp Litopenaeus vannamei. (30th July 2020) - Guo, Jingping; Zhou, Wanyou; Liu, Shasha; Zhang, Wenbing; Mai, Kangsen
Abstract: An 8‐week growth trial was conducted to evaluate the efficacy of crystalline methionine (C‐Met) or microencapsulated methionine (M‐Met) in practical diets for Pacific white shrimp Litopenaeus vannamei . A high fishmeal reference diet was formulated with 15% fishmeal, and then, soybean meal (SBM) was used to replace 50% fishmeal as a low fishmeal basal diet (7.5% fishmeal). Graded levels (0.1%, 0.15% and 0.2%) of methionine originating from C‐Met or M‐Met were added to the basal diet. Each diet was randomly assigned to three tanks (40 shrimps per tank) in an indoor flow through seawater system. The results showed that the shrimp fed the basal diet with 0.15% or 0.20% methionine originating from 0.375% or 0.5% M‐Met had significantly higher final weight and weight gain as compared to shrimp fed the basal diet. The supplementation M‐Met in the basal diets resulted in increased serum ammonia in shrimp. Hepatopancreas amylase activity of shrimp showed a decreasing trend with increasing methionine supplementation, which is in contrast with the upswing trend in trypsin at pancreatic segment. This study indicated that the diets supplemented with 0.15% or 0.20% of methionine from M‐Met (0.58% or 0.65% of dietary methionine respectively) were effective in improving the nutritional value of SBM‐based diets deficient in methionine (0.48%) for the Pacific white shrimp.